Can A Theoretical Consideration of Australia's Anti-Discrimination Laws Inform Law Reform?. (March 2013) - Hewitt, Anne
Anti-discrimination law in Australia is at a crossroads. After four decades of proliferation of legislation to regulate discrimination, national attention has turned from increasing regulation to legislative consolidation and reform. This article contributes a theoretical analysis to the reform debate. Two liberal theoretical justifications for prohibiting discrimination, harm and redistributive justice, are considered. This investigation assists to determine when the state should intervene in order to restrict discrimination, and whether state and territory anti-discrimination regimes have a legitimate continuing role in Australia's legislative landscape.